[N′-(4-Decyloxy-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato-κ3N,O,O′]dimethyltin(IV): crystal structure and Hirshfeld surface analysis - Rosely, S.N.M.; Hussen, R.S.D.; Lee, S.M.; Halcovitch, N.R.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2017)
The title diorganotin compound, [Sn(CH3)2(C28H32N2O4)], features a distorted SnC2NO2 coordination geometry almost inter-mediate between ideal trigonal-bipyramidal and square-pyramidal. The dianionic Schiff base ligand coordinates in a tridentate fashion via two alkoxide O and hydrazinyl N atoms; an intra-molecular hy-droxy-O - H...N(hydrazin-yl) hydrogen bond is noted. The alk-oxy chain has an all-trans conformation, and to the first approximation, the mol-ecule has local mirror symmetry relating the two Sn-bound methyl groups. Supra-molecular layers sustained by imine-C - H...O(hy-droxy), π-π [between dec-yloxy-substituted benzene rings with an inter-centroid separation of 3.7724 (13) Å], C - H...π(arene) and C - H...π(chelate ring) inter-actions are formed in the crystal; layers stack along the c axis with no directional inter-actions between them. The presence of C - H...π(chelate ring) inter-actions in the crystal is clearly evident from an analysis of the calculated Hirshfeld surface.